2015
DOI: 10.1007/s00421-015-3299-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary capillary reserve and exercise capacity at high altitude in healthy humans

Abstract: PurposeWe determined whether well-acclimatized humans have a reserve to recruit pulmonary capillaries in response to exercise at high altitude.MethodsAt sea level, lung diffusing capacity for carbon monoxide (DLCO), alveolar-capillary membrane conductance (DmCO), and pulmonary capillary blood volume (Vc) were measured at rest before maximal oxygen consumption () was determined in seven adults. Then, DLCO, DmCO and Vc were measured pre- and post-exhaustive incremental exercise at 5150 m after ~40 days of acclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(73 reference statements)
2
11
0
Order By: Relevance
“…Interestingly, Taylor et al showed that recruitment of pulmonary capillaries in response to exercise at high altitude is limited and may therefore be a significant source of exercise limitation [78]. This is keeping with previous correlation found between lung diffusing capacity for nitric oxide (DL NO ) and VO 2 max at altitude [7,8,74].…”
Section: Lung Diffusion Capacitysupporting
confidence: 57%
“…Interestingly, Taylor et al showed that recruitment of pulmonary capillaries in response to exercise at high altitude is limited and may therefore be a significant source of exercise limitation [78]. This is keeping with previous correlation found between lung diffusing capacity for nitric oxide (DL NO ) and VO 2 max at altitude [7,8,74].…”
Section: Lung Diffusion Capacitysupporting
confidence: 57%
“…More importantly, the reaction of NO with Hb solutions is 500-1000 times faster than its reaction with blood from animal [23] or human [24] sources. Therefore, θNO cannot be "infinite", as originally thought [10,12] or more recently claimed [18,19]. Further support for a "finite" θNO value comes from physiological experiments where the red cell was "by-passed", either by adding free Hb (by haemolysis) or a haem-based blood substitute to the membrane oxygenator perfusate, or by exchange transfusion of dogs with chemically stabilised bovine haemoglobin (Oxyglobin TM ).…”
Section: Determinants Of No Uptakementioning
confidence: 90%
“…[11] yielded strong correlations between DLNO (as a surrogate for DMNO) and DMCO for experimental data at rest and at exercise [35,36,109]. Others (for example [18,62,63,94]) preferred the later formula given by FORSTER [4], but negative or excessively high DMCO values have been observed with its use [19]; thus, some [19,25] favoured the formula given by REEVES and PARK [26] and "best fit" α-ratios (all >2.0) for getting the best agreement for DMCO between , with the corresponding LLN, ULN and z-score (standardised residuals: number of standard deviations above or below the reference value) Report alveolar volume in L BTPS and as TLC % pred NO: nitric oxide; O 2 : oxygen; θCO (NO): specific conductance in the blood for carbon monoxide (NO) in mL·(mL blood·min·mmHg) −1 ; DMCO: alveolar-capillary membrane diffusing capacity for CO; PO 2 : oxygen tension; PAO 2 : alveolar oxygen tension; Hb: haemoglobin; DMNO: alveolarcapillary membrane diffusing capacity for NO; KNO: rate of change of NO from alveolar gas; KCO: rate of change of CO from alveolar gas; LLN: lower limit of normal; ULN: upper limit of normal; BTPS: body temperature and pressure, saturated (760 mmHg, 37°C, 100% humidity); TLC: total lung capacity. # : used in tables 1, 2 and 3 and the supplementary appendices.…”
Section: Evaluating the Measurement Of Dlno Repeatability Reproducibmentioning
confidence: 98%
See 2 more Smart Citations